Growth and Development of the Lymphoid Organs as Affected by Inorganic and Organic Zinc in Broilers Chickens - Bulao, Maria Fe (JPAIR Multidisciplinary Research, 2015)
Zinc is one of the important minerals that affect the immune system. It should be incorporated in the diet since the effects of deficiency are very pronounced. However, the levels and sources are still unknown particularly in the growth and development of the lymphoid organs. Hence, this study was conducted. Two experiments were conducted following a completely randomized design for a period of 36 days. Experiment 1 utilized zinc oxide while 2 made used of zinc methionine. Results revealed that the different levels of zinc oxide did not affect the average weight and number of lymphatic nodules of the Bursa of Fabricius and thymus. The same organs involuted between 15-28 days and 11-21 days, respectively. The spleen, however, was unaffected. In Experiment 2, it shows that the average weight and number of lymphatic nodules of the bursa of Fabricius and thymus were not affected by the different levels of zinc methionine. Bursa involuted from days 8-28 while thymus, between 11-21 days. Increasing spleen’s weight pattern was noted only in the control group beginning on day 11 and peak on day 28. The study concludes that the growth and development of the lymphoid organs were not affected by zinc inclusion in the diet. It recommends that supplementation must be accompanied by good management practices.